2019
DOI: 10.5194/tc-13-2111-2019
|View full text |Cite
|
Sign up to set email alerts
|

Arctic freshwater fluxes: sources, tracer budgets and inconsistencies

Abstract: Abstract. The net rate of freshwater input to the Arctic Ocean has been calculated in the past by two methods: directly, as the sum of precipitation, evaporation and runoff, an approach hindered by sparsity of measurements, and by the ice and ocean budget method, where the net surface freshwater flux within a defined boundary is calculated from the rate of dilution of salinity, comparing ocean inflows with ice and ocean outflows. Here a third method is introduced, the geochemical method, as a modification of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
4
12
0
Order By: Relevance
“…The freshwater input from Arctic glaciers and the Greenland Ice Sheet comprises a minor but difficult to compute source of freshwater in the Arctic Ocean basin. The Greenland Ice Sheet and the surrounding smaller peripheral glaciers and ice caps on Greenland have shown an increasing tendency for net ice sheet loss since the early 2000s (Shepherd et al, 2020;Noël et al, 2017;Bolch et al, 2013), though with wide spatial and large temporal variability from year to year, a trend reflected in other glaciated basins within the Arctic including Arctic Canada, Russia, and Svalbard (e.g., Gardner et al, 2011;Moholdt et al, 2012). The Ice sheet Mass Balance Intercomparison Exercise (IMBIE) (Shepherd et al, 2012) and IMBIE2 (Shepherd et al, 2020) results show, for example, a steady increase in net mass loss from around −119 ± 16 Gt yr −1 for the 1992-2011 period to −244 ± 28 Gt yr −1 in the 2012-2017 period with a peak in 2012 of 345 ± 66 Gt yr −1 (see also Helm et al, 2014).…”
Section: Freshwater Flux From Glaciers and The Greenland Ice Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…The freshwater input from Arctic glaciers and the Greenland Ice Sheet comprises a minor but difficult to compute source of freshwater in the Arctic Ocean basin. The Greenland Ice Sheet and the surrounding smaller peripheral glaciers and ice caps on Greenland have shown an increasing tendency for net ice sheet loss since the early 2000s (Shepherd et al, 2020;Noël et al, 2017;Bolch et al, 2013), though with wide spatial and large temporal variability from year to year, a trend reflected in other glaciated basins within the Arctic including Arctic Canada, Russia, and Svalbard (e.g., Gardner et al, 2011;Moholdt et al, 2012). The Ice sheet Mass Balance Intercomparison Exercise (IMBIE) (Shepherd et al, 2012) and IMBIE2 (Shepherd et al, 2020) results show, for example, a steady increase in net mass loss from around −119 ± 16 Gt yr −1 for the 1992-2011 period to −244 ± 28 Gt yr −1 in the 2012-2017 period with a peak in 2012 of 345 ± 66 Gt yr −1 (see also Helm et al, 2014).…”
Section: Freshwater Flux From Glaciers and The Greenland Ice Sheetmentioning
confidence: 99%
“…Glaciers in the Canadian Arctic Archipelago draining into the same region as northern Greenland have seen a succession of ice shelf collapses and associated changes in the fjords most likely related to sub-shelf melting and increased atmospheric air temperatures in the region since the 1950s (e.g., Copland et al, 2007;Gardner et al, 2011). Glaciers in Svalbard (e.g., Noël et al, 2020) and the high Russian Arctic have also shown consistent mass loss trends (e.g., Moholdt et al, 2012), indicating an increase in freshwater contribu-tion from the smaller Arctic glaciers in the region directly into the Arctic Ocean basin, but their contribution is an order of magnitude smaller than from Greenland.…”
Section: Freshwater Flux From Glaciers and The Greenland Ice Sheetmentioning
confidence: 99%
“…A n t hr op o g e n i c c l i m a t e c ha n g e l e a d s t o r a p i d transformations in the Arctic Ocean, including Atlantic Water transport of heat and anthropogenic carbon, increased sea-ice melt, as well as changes in the meteoric water budget (Muilwijk et al, 2018;Arthun et al, 2019;Forryan et al, 2019;Terhaar et al, 2020;Timmermans and Marshall, 2020;Wang et al, 2020). Via the Canadian Arctic Archipelago, the Barents Sea, and Fram Strait, the Arctic Ocean is connected to the North Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity and stable oxygen isotopes (d 18 O) allow to determine fractions of sea-ice melt and meteoric water (comprising precipitation, river runoff, and glacial meltwater) (Dodd et al, 2009). Atlantic-and Pacific-derived waters have classically been distinguished by nutrient-based methods using nitrate-phosphate (N:P method) or phosphate-oxygen relationships (PO*; e.g., Ekwurzel et al, 2001;Yamamoto-Kawai et al, 2008;Jones et al, 2008a;Jones et al, 2008b;Bauch et al, 2011;Dodd et al, 2012;Newton et al, 2013;Alkire et al, 2015;Alkire et al, 2019;Forryan et al, 2019). However, there is an ongoing debate regarding the reliability of nutrient-based approaches for Arctic Ocean water masses, due to shelf-interaction processes taking place on the broad Arctic shelves such as denitrification in the Chukchi Sea, or seasonal variability (Ekwurzel et al (2001); Bauch et al (2011); Alkire et al (2015); Alkire et al (2019); Forryan et al (2019)).…”
Section: Introductionmentioning
confidence: 99%
“…Is "ocean freshwater flux" purely a mirage, therefore? Forryan et al (2019) pursue the surface freshwater flux approach, noting that (as is well known, e.g. Östlund and Hut, 1984) evaporation and freezing are distillation processes that leave behind a geochemical imprint via oxygen isotope anomalies on the affected freshwater in the sea ice and seawater, and also take away the inverse imprint on water that is evaporated away from the sea surface, to reappear as precipitation, river runoff or other terrestrial glacial input, or is convected out of sea ice as brine.…”
mentioning
confidence: 99%